PENGARUH PELATIHAN METODE E-LEARNING TERHADAP KOMPETENSI PESERTA PELATIHAN : STUDI KASUS PADA PT VIDASKILL SOLUTION INDONESIA - Faridah Faridah; Yoeliastuti Yoeliastuti (JURNAL LENTERA BISNIS, 2025)
E-learning method is a learning process that utilizes sophisticated technology where learning activities are carried out online. online learning is equipped with various tools that can be used in learning activities or training for training institutions, such as communication and interaction activities, conducting question and answer sessions, and asking questions to trainers or vice versa. The purpose of the study was to analyze the effect of the e-learning method as a training medium on the competence of participants from various groups. the research method uses a descriptive quantitative method, with sampling using saturated sampling (census), where the population is used as a research sample. to obtain data using a likert scale by distributing questionnaires to all participants who have participated in training with the e-learning system. the data that has been collected is then processed with the spss 25 application, using simple linear regression. for data analysis with validity and reliability tests, and classical assumption tests, normality tests, linearity tests and heteroscedasticity. based on the results of the research data processing, it can be concluded that the training system with the e-learning method has an effect on increasing the competence of training participants by 0.460 or 46%.